The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1136/bmjopen-2011-000622
|View full text |Cite
|
Sign up to set email alerts
|

Antiemetic treatment for acute gastroenteritis in children: an updated Cochrane systematic review with meta-analysis and mixed treatment comparison in a Bayesian framework

Abstract: ObjectiveTo assess the evidence for the safety and effectiveness of antiemetics on gastroenteritis-induced vomiting in children and adolescents.DesignSystematic review.Data SourcesThe Cochrane Central Register of Controlled Trials, MEDLINE and EMBASE searched from 1980 to March 2012.MethodsMethods included comprehensive searches, data synthesis, meta-analysis and mixed treatment comparisons (MTC).Review methodsReference lists were checked, and missing or inconsistent data were sought from trial investigators. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
43
3
13

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 28 publications
5
43
3
13
Order By: Relevance
“…This means that, in an ED setting, 6 out of 10 children aged 1–6 years with vomiting due to AGE and no or mild to moderate dehydration, can be successfully treated with oral rehydration solution alone, without the need for drugs. This finding is consistent with the estimates of the Cochrane review [17, 18]. …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This means that, in an ED setting, 6 out of 10 children aged 1–6 years with vomiting due to AGE and no or mild to moderate dehydration, can be successfully treated with oral rehydration solution alone, without the need for drugs. This finding is consistent with the estimates of the Cochrane review [17, 18]. …”
Section: Discussionsupporting
confidence: 92%
“…Hospital admission rates are lower in the ondansetron group vs both domperidone and placebo. Differences among groups did not reach the statistical significance of the meta-analysis (RR 0.41; 95% IC 0.29 to 0.59) [18]. In the present study, the need for observation stay to last more than six hours is statistically significantly lower in the ondansetron group compared with the domperidone and placebo groups.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…The return visits to ED were comparable between the study groups at the 24-hour follow-up. This trial [6] has been considered to have reported incoherent data with inflated treatment effect [14]. Pediatric viral GE is a self-limited disease [15].…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] Ondansetron, an antiemetic agent that is increasingly employed in the ED to prevent emesis, 12,13 is now routinely administered to children with vomiting because of acute gastroenteritis, a common intercurrent illness in children. [8][9][10][11][14][15][16] In Europe, gastroenteritis is estimated to cause 14.1% of pediatric diabetic ketoacidosis (DKA). 17 Because ondansetron is nonsedating and is anecdotally increasingly used in children with T1DM, we sought to determine if its administration to children with T1DM presenting for ED care with vomiting because of intercurrent illness is associated with improved clinical outcomes.…”
mentioning
confidence: 99%